The Indonesian Second Person Terms Of Address Used By Undergraduate Students of Petra Christian University in Social Network Sites and Face-To-Face Interaction towards Their Intimate and Distant Friends - Noviyana Sugianto; Flora Debora Floris (Institute of Research and Community Outreach - Petra Christian University, 2014)
The study deals with Indonesian second person terms of address used in social network sites and face-to-face interaction. The purpose of the study was to observe the use of Indonesian second person terms of address used by the respondents to address their intimate and distant friends when they communicated in social network sites and face-to-face interaction. The findings showed that there were 7 of 10 categories of Indonesian second person terms of address used by the respondents towards their intimate and distant friends in social network sites and face-to-face interaction. In conclusion, there was no significant difference in the use of the Indonesian second person terms of address used by the respondents in social network sites and face-to-face interaction toward their intimate and distant friends